THE EMPOWERMENT OF MOSLEM BOARDING SCHOOL FOR THE SUSTAINABLE PREVENTION AGAINST SCABIES DIEASE - Nugroho Nur Ponco; Zaenal Fanani (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2019)
Pondok Pesantren Tebuireng Jombang is a recognizable Moslem Boarding School in Jombang which is occupied by 4,560 students. It involves 3,230 males and 1,530 females. Empowerment is needed in terms of social, economic and culture. The most dominant issue is the cleanliness or sanitation of the environment of boarding school or of the students. Both are classical issues at Pondok Pesantren Tebuireng Jombang. Environment sanitation is emphasized on skin health due to the risk of scabies disease. Location of research is Pondok Pesantren Tebuireng Jombang. The object of research includes all staffs, employees, leaders and students of Pondok Pesantren Tebuireng Jombang. The ultimate goal of this research is to formulate the model of human resource empowerment at Pondok Pesantren Tebuireng Jombang to support sustainable environmental management for scabies disease prevention. Data are analyzed using a model of generalized structure component analysis (GesCA). Based on the result of research and discussion, it is concluded that Organization factor is influential directly, but insignificantly, to environmental sustainability. Organization factor is influential indirectly but significantly, through human resource empowerment, to environmental sustainability freed from scabies disease. Keywords: Boarding School, scabies disease, human resource